Age at menarche and early menarche among healthy adolescents - Annang Giri Moelyo; Anindita Wulandari; Oktania Imas; Ulfa Puspita Rahma; Nurul Hidayah; Cempaka Kesumaningtyas; Fadhilah Tia Nur; Hari Wahyu Nugroho (Paediatrica Indonesiana, 2019)
Background Menarche is an important indicator of female adolescents' health and also population health. Age at menarche tends to decrease in many countries. Early menarche that defined from the lowest quartile of age at menarche, associated with some physical and psychological problems. Objective To determine the mean age at menarche, the prevalence of early menarche among healthy adolescents in Surakarta and its association to nutritional status. Methods This cross-sectional study was conducted in 5 schools (3 junior and 2 senior high schools) in Surakarta, Central Java, Indonesia, from September 2016 to March 2018, by consecutive sampling technique. We included menarched healthy female students whose parent provided informed consent and without consuming any routine medication. Data were derived from self-reported questionnaire and measurements of body weight; body height; and body mass index (BMI) by calculated based on weight/height2(kg/m2). Results Of 835 eligible subjects, the mean age at menarche was 12.0 (SD 1.1) years (range 8.8-15.1 years) and the prevalence of early menarche was 11.1%. The peak of age at menarche were at 11,12, and 13 years (24.3%, 36.2%, and 23.9%, respectively) and almost 99.04% of subjects had menarche at 14 years old. The proportion of early menarche between subjects birth 1997-2001 and 2002-2007 were 8.4% and 16.1%. Early menarche associated with overweight-obese in adolescents (odd ratio 2.14; 95%CI 1.21 to 3.76). Conclusion The mean age at menarche of healthy adolescents in Surakarta is younger than other previous studies in Indonesia. Early menarche was significantly a risk for overweight/obese in adolescents.